New names in Myrcia sect. Calyptranthes (Myrtaceae) - Lima, Duane F.; Lucas, Eve J.; Lima Lourenço, Ana Raquel; Mazine, Fiorella F. (Phytotaxa, 2020)
After extensive molecular (Staggemeier et al. 2015; Santos et al. 2017; Wilson et al. 2016) and revisionary (e.g. Lima et al. 2018; Lourenço et al. 2018) work to maintain a manageable and monophyletic genus, Myrcia De Candolle (1827: 406) currently includes the previously recognized genera Calyptranthes Swartz (1788: 79), Gomidesia O.Berg (1855: 5) and Marlierea Cambessèdes (1832–1833: 373) (see Lucas et al. 2018). The majority of Calyptranthes species are now considered part of Myrcia sect. Calyptranthes (Sw.) A.R.Lourenço & E.Lucas (in Lucas et al. 2018: 3). As a result, Lourenço et al. (2018) recently transferred the continental species of Calyptranthes to Myrcia. Among these new names, two were subsequently found to be illegitimate and are herein corrected. The remaining species of Calyptranthes, mostly from the islands of the Caribbean, were transferred by Campbell et al. (2019).